2021
DOI: 10.1080/09636412.2021.1976822
|View full text |Cite
|
Sign up to set email alerts
|

Legacies of Wartime Order: Punishment Attacks and Social Control in Northern Ireland

Abstract: Many armed groups create informal institutions to maintain social order during conflict. The remnants of these informal institutions form a key challenge for governments in postconflict societies in their attempts to reestablish themselves as credible state authorities. The persistence of paramilitary groups' informal "justice" systems in the form of so-called punishment attacks in Northern Ireland, more than twenty years on from the Good Friday Agreement, offers insights into the legacy of wartime institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…These are attacks directed at the groups' 'own' communities (ingroup attacks). In previous research, we showed that there is a correlation between areas experiencing such present-day social control by armed groups and their social control during the conflict (Rickard and Bakke 2021). We sampled census tract areas, known as Super Output Areas (SOAs), that are worst affected by paramilitary-style attacks between 2008 and 2018 (there are 890 SOAs in Northern Ireland, with an average population of 2,000 people).…”
Section: Methodsmentioning
confidence: 99%
“…These are attacks directed at the groups' 'own' communities (ingroup attacks). In previous research, we showed that there is a correlation between areas experiencing such present-day social control by armed groups and their social control during the conflict (Rickard and Bakke 2021). We sampled census tract areas, known as Super Output Areas (SOAs), that are worst affected by paramilitary-style attacks between 2008 and 2018 (there are 890 SOAs in Northern Ireland, with an average population of 2,000 people).…”
Section: Methodsmentioning
confidence: 99%
“…Ellison et al (2012) discuss how it took nearly a decade after the Agreement was signed before Sinn Fein accepted the new Police Force in Northern Ireland as legitimate. Rebel governance provided local policing in the absence of the o¢ cial police force and indeed the evidence is that continues to be relevant today even if the o¢ cial police force is o¢ cially recognised (Ulezic (2019) and Rikard and Bakke (2021)). An imperfect peace in the form of the Belfast Agreement was signed in 1998, but it was eight years before the St. Andrews Agreement was signed in 2006 which aimed to resolve hanging issues of policing and commitment to the power-sharing executive.…”
Section: After the 1998 Agreementmentioning
confidence: 99%
“…14 An additional layer is the broader legacy of Northern Ireland's political context, including the enduring presence of paramilitary organizations that exert significant influence over social structures. 15 Highlighting the ways in which 'the past is lived in the present', 16 historical patterns of gender inequality and militarized sectarian division continue to shape women's experience of public life, as well as the ways in which related threats are subjectively understood. 17 Participants reported multiple interactions where they understood, and were made to understand, seemingly innocuous statements as threats, such as ostensibly throwaway comments made about their 'lovely set of windows', and about how someone 'knew them' or 'knew what they were doing' or how they 'recognized their accents'.…”
Section: Defining Threatsmentioning
confidence: 99%